Evaluation method and application for in-situ stress in No. 8+9 coal seam, southern Shenfu block, northeastern margin of Ordos Basin - Jiawei WU; Wei TANG; Yanhe ZHU; Cunwu WANG; Yongjing TIAN; Jingyu ZI; Jianghao YANG; Xian SHI (Shiyou shiyan dizhi)
The direction and magnitude of the present in-situ stress influence the propagation of hydraulic fractures in coal seams, making it a key geological parameter for coalbed methane (CBM) well network deployment and fracturing design. Accurate evaluation of the present in-situ stress direction and magnitude in coal seams is crucial for CBM exploration and development. This study focused on the direction and magnitude of the current in-situ stress in the No. 8+9 coal seam in the southern Shenfu block, northeastern margin of the Ordos Basin. Array acoustic logging, microseismic monitoring, and imaging logging were used to evaluate the direction of the present maximum horizontal principal stress in the coal seam and its roof and floor. Under constraints of the current in-situ stress magnitude from injection/falloff tests, parameters for the composite spring model were determined, and the current in-situ stress magnitude was further calculated. The results showed that the direction of the present maximum horizontal principal stress for the No. 8+9 coal seam and its roof and floor in the eastern part of the study area was nearly in the NNE orientation. In the western part, the directions of the maximum horizontal principal stress may deviate due to stress field disturbances around inactive faults and hydraulic fracturing activities. In 20 wells, calculations of the in-situ stress showed that the vertical principal stress in the No. 8+9 coal seam with a vertical depth of 1 902-2 181 m was 47-54 MPa. The minimum horizontal principal stress was 35-44 MPa, and the maximum was 42-50 MPa. With a lateral pressure coefficient less than 1, it was in the normal faulting stress state. In the eastern part of the study area, the NNE-oriented maximum horizontal principal stress was sequentially evolved from the SN-oriented compression during the Meso-Cenozoic Indosinian stage, the NNW-oriented compression during the Yanshanian stage, and the NNE-oriented compression during the Himalayan stage. Considering the distribution of natural fractures with an average NNW orientation during different tectonic stages, as well as the propagation pattern of NNE-oriented vertical hydraulic fractures under the normal faulting stress state with NNE-oriented maximum principal horizontal stress in the eastern fracture prediction area, it was recommended to deploy horizontal cluster wells within the azimuthal interval perpendicular to the current NNE-oriented maximum horizontal principal stress direction and the average NNW-oriented natural fracture direction. This approach aims to enhance production through large-scale extreme volume fracturing in horizontal wells by integrating the productivity of natural fractures and induced hydraulic fractures. In addition, the in-situ stress direction and natural fracture parameters should be further characterized in detail to guide fracturing design and improve CBM production.